Answer:
(-2, -4)
Step-by-step explanation:
–2x + 2y = -4
3х + Зу = -18
Divide the first equation by 2
–2x/2 + 2y/2 = -4/2
-x +y = -2
Divide the second equation by 3
3х/3 + Зу/3 = -18/3
x + y = -6
Add these equation together
-x +y = -2
x + y = -6
-------------------
0x + 2y = -8
2y = -8
Divide each side by 2
2y/2 = -8/2
y = -4
Now we need x
x+y = -6
x-4 = -6
Add 4 to each side
x-4+4 = -6+4
x = -2
Answer:
Step-by-step explanation:
If the roots are 1 + 5i and 1 - 5i, then you need the factors that result from those roots. They are (x - 1 + 5i) and (x - 1 - 5i). Now what you do with those is FOIL them out. Doing that gives you the following:
(what a mess, huh?)
The good thing is that several of those terms cancel each other out. +5ix cancels out the -5ix; -5i cancels out the 5i; and the 2 -x terms combine to -2x. That leaves you with:
![x^2-2x-25i^2](https://tex.z-dn.net/?f=x%5E2-2x-25i%5E2)
Obviously you're in the section in math that deals with complex (imaginary) numbers so you should know that i-squared is equal to -1. Making that replacement:
![x^2-2x+25](https://tex.z-dn.net/?f=x%5E2-2x%2B25)
a = 1, b = -2, c = 25
First, conceptually understand what an inverse function is, it makes solving it very intuitive. An inverse function is simply a function which has points (y,x) for every point (x,y) of the parent function. So you are essentially taking all points of the parent function and switching the x and y coordinates for each. Those switched coordinates are produced by the "inverse function".
Mathematically then, finding the inverse function is a matter of solving for x and then switching the variable labels. In this case:
y=2x+1 subtract 1 from both sides
y-1=2x divide both sides by 2
(y-1)/2=x now just switch the labels for the variables...
y=(x-1)/2 so
f^-1(x)=(x-1)/2 is the inverse of f(x)=2x+1
Answer:
32ft of chain divided by 14ft pieces... that's two pieces of chain
Step-by-step explanation: